Comparison of Dentoalveolar Expansion with Clear Aligners by Using Two Different Treatment Protocols in the Early Mixed Dentition: A Retrospective Study - Nurver Karslı; Zehra Yurdakul; Gözde Çobanoğlu; Ebru Çetinkaya Tokmak; Hakan Gogen (European Annals of Dental Sciences)

(untitled)
Objectives: To evaluate the effect of different expansion protocols on tooth movements during maxillary arch expansion with Invisalign First System® (IFS) in the mixed dentition.Materials and Methods: This study was conducted using digital models of 20 patients treated with sequential expansion (MFE, mean age: 7.88±0.60; 9 girls, 11 boys) and 20 patients treated with simultaneous expansion (SIE, mean age: 7.94±0.51; 12 girls, 8 boys) acquired before (T0) and after (T1) treatment. Maxillary parameters were measured on each model at T0 and T1. Mann Whitney U tests were used for comparisons between groups, and Wilcoxon tests were used for the analysis of intra-group.Results: In both groups, the greatest increase of maxillary arch width (AW) was determined at both the cusp tips and gingival levels of the upper first deciduous molars followed by the second deciduous molars and by the deciduous canines (p < 0.01). The lowest increase of AW was found in the at the permanent first molars (p < 0.01). Conclusion: Both protocols with IFS can be considered effective in patients in early mixed dentition. The greatest increase was detected at the level of the upper first deciduous molars, whereas the least increase was observed at the level of the first permanent molars.Key Words: Clear Aligners, Invisalign® First system, Mixed dentition